Alloy stainless steel wire and preparation process
By adding high-hardness carbides and other metal powders to nickel-cobalt alloy stainless steel wire and adopting specific preparation processes, the problems of insufficient oxidation and wear resistance of existing stainless steel wires in high humidity and high temperature environments are solved, and its hardness, wear resistance and high temperature performance are significantly improved.
Patent Information
- Application Number
- CN202510175920.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-18
- Publication Date
- 2025-04-25
AI Technical Summary
The oxidation resistance and wear resistance of existing nickel-cobalt alloy stainless steel wires in high humidity and high temperature environments need to be improved.
By adding high-hardness carbides such as WC, Cr3C2, TaC, as well as Re, Ru, rare earth alloys and graphite powders, an alloy stainless steel wire was prepared, and the process steps such as wet ball milling, vacuum drying and high-temperature smelting were used to improve its hardness, wear resistance and high-temperature performance.
It significantly improves the hardness and wear resistance of alloy stainless steel wire, enhances its dimensional stability and deformation resistance at high temperatures, and improves corrosion resistance and oxidation resistance at high temperatures.
Smart Images

Figure CN119876772A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of alloy stainless steel wires, in particular to an alloy stainless steel wire and a preparation process thereof. Background Art
[0002] Stainless Steel is the abbreviation of stainless acid-resistant steel. Steel that is resistant to weak corrosive media such as air, steam, and water or has stainless properties is called stainless steel; and steel that is resistant to chemical corrosive media (acids, alkalis, salts, etc.) is called acid-resistant steel. Stainless steel wire is also called stainless steel wire, which is a silk product of various specifications and models made of stainless steel as raw material. Nickel-cobalt alloy stainless steel wire, nickel has the effect of corrosion resistance, and cobalt has the effect of solid solution strengthening, which gives steel hot hardness and improves the high-temperature performance of steel. Due to its excellent mechanical properties, electrical properties, welding properties and corrosion resistance, stainless steel wire has gained a huge application space in the fields of functional composite materials, corrosion-resistant materials, conductive materials and information materials.
[0003] The Chinese patent with publication number CN114700383B discloses a nickel-cobalt alloy stainless steel wire, which is prepared by weight percentage as follows: iron Fe: 0.001-1.25%, cobalt Co: 1.22-1.25%, chromium Cr: 10-20%, molybdenum Mo: 1-5%, neodymium Nb + tantalum Ta: 4-6%, aluminum Al: 0.001-3%, titanium Ti: 0.001-2%, carbon C: 0.001-0.1%, phosphorus P: 0.01-0.03%, magnesium Mg: 0.001-0.01%, boron B: 0.001-0.02%, zirconium Zr: 0.001-0.1 %, silicon Si: 3-8%, and the balance is nickel Ni. The nickel-cobalt alloy stainless steel wire and its production process improve the oxidation resistance of the nickel-cobalt alloy stainless steel wire in harsh environments such as high humidity and high temperature. Moreover, the drawing cooling device is used to cool the nickel-cobalt alloy stainless steel wire after drawing, thereby preventing the nickel-cobalt alloy stainless steel wire from shrinking and breaking or being scratched during the winding process, and also plays the role of cleaning and lubricating the nickel-cobalt alloy stainless steel wire. However, the wear resistance of the alloy stainless steel wire prepared by the above process needs to be further improved. Therefore, in order to solve the above-mentioned problems, the present invention provides an alloy stainless steel wire and a preparation process. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides an alloy stainless steel wire and a preparation process, which solves the problems mentioned in the above background technology.
[0005] To achieve the above purpose, the present invention is implemented by the following technical scheme: an alloy stainless steel wire is made of the following raw materials in parts by weight: 8.5-12.5 parts of WC powder, 5.5-9.5 parts of Co powder, 2.5-6.5 parts of Cr3C2 powder, 0.35-0.65 parts of TaC powder, 3.5-7.5 parts of Re powder, 1.5-4.5 parts of Ru powder, 5.5-8.5 parts of rare earth alloy powder, and 8.5-12 parts of graphite powder; The rare earth alloy powder is composed of a mixture of Cu, Ce and La, and the mass ratio thereof is 0.8:(0.3-0.5):(1.2-1.6).
[0006] A preparation process of alloy stainless steel wire specifically comprises the following preparation steps: Step 1, pouring anhydrous ethanol into polyethylene glycol, and performing ultrasonic dispersion treatment to obtain a mixed solution; Step 2: Add nano hexagonal boron nitride to the mixed solution of step 1, and continue ultrasonic treatment; Step 3, adding the weighed powders and then dispersing by ultrasonic treatment; Step 4: After being evenly dispersed, wet ball milling is used, and then drying is carried out in a vacuum drying furnace, and then sieving is carried out using a sieve; Step 5, pouring into a high-temperature melting furnace for heating and melting, and then sequentially performing desulfurization, deoxidation, alloying, and refining with a refining agent to obtain stainless steel wire; Step 6: Heat the prepared stainless steel wire to 400-600°C and then soak it in an alkaline mixed solution for 30-60 minutes, then wash it with water, dry it, and then draw it to obtain alloy stainless steel wire.
[0007] Preferably, in step 1, the ultrasonic dispersion treatment is performed for 10-15 min.
[0008] Preferably, in step 2, the ultrasonic dispersion treatment is performed for 25-35 minutes.
[0009] Preferably, in step three, the ultrasonic dispersion treatment is performed for 30-40 minutes.
[0010] Preferably, in step 4, the ball milling time is 66-72 hours, the drying temperature is 110-120° C., the drying time is 10-12 hours, and the sieve is selected from 100-120 mesh.
[0011] Preferably, in step six, the formula of the alkaline mixed solution is as follows by mass percentage: NaOH 75%-80%, NaNO3 20%-25%.
[0012] Preferably, in step six, deionized water is used for washing 3-5 times.
[0013] Preferably, the feed ratio (ml:mL:g) of anhydrous ethanol, polyethylene glycol and nano hexagonal boron nitride is: (50-75): (25-40): (2.4-3.5g).
[0014] Beneficial Effects The invention provides an alloy stainless steel wire and a preparation process. Compared with the prior art, the invention has the following beneficial effects: the alloy stainless steel wire and preparation process can effectively improve the hardness and wear resistance of the stainless steel wire by adding high-hardness carbides such as WC, Cr3C2, TaC, etc., so that the stainless steel wire can maintain good performance in a wear environment, and these carbides have a high melting point and thermal stability, which can improve the dimensional stability and deformation resistance of the stainless steel wire at high temperatures; Co, as a bonding phase, can enhance the bonding force of the alloy phase and improve the strength and toughness; Re and Ru can improve the crystal structure, enhance the dislocation resistance, further enhance the strength and toughness, and can improve the high-temperature oxidation resistance of the alloy, form a stable oxide film, and prevent further oxidation; Cr in Cr3C2 can form a passivation film on the surface to improve corrosion resistance; rare earth elements Ce and La can refine the grains, improve the surface state, enhance the stability of the passivation film, improve the corrosion resistance, and can improve the physical properties such as the magnetism of the alloy, thereby expanding the application of the alloy stainless steel wire in the fields of electronics and electrical engineering; graphite powder can play the role of a solid lubricant, reduce the friction coefficient, improve the processing performance, make the drawing and other processing processes smoother, and reduce the wear of the mold. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 A comparison chart of wear resistance test provided for an alloy stainless steel wire and its preparation process of the present invention. DETAILED DESCRIPTION
[0016] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0017] Example 1 A preparation process of alloy stainless steel wire specifically comprises the following preparation steps: Step 1: Pour 50 mL of anhydrous ethanol into 25 mL of polyethylene glycol, and perform ultrasonic dispersion treatment for 10 minutes to obtain a mixed solution; Step 2: Add 2.4 g of nano hexagonal boron nitride to the mixed solution of step 1, and continue ultrasonic treatment for 25 min; Step 3, add the weighed powders: WC powder 8.5g, Co powder 9.5g, Cr3C2 powder 6.5g, TaC powder 0.65g, Re powder 7.5g, Ru powder 4.5g, rare earth alloy powder 8.5g, graphite powder 12g, wherein the rare earth alloy powder is composed of a mixture of Cu, Ce, and La, and the mass ratio thereof is 0.8:0.3:1.2, and then ultrasonically disperse for 30min; Step 4: After being evenly dispersed, wet ball milling is performed for 66 hours, and then placed in a vacuum drying furnace at 110°C for 10 hours, and then sieved with a 100-mesh screen; Step 5, pouring into a high-temperature melting furnace for heating and melting, and then sequentially performing desulfurization, deoxidation, alloying, and refining with a refining agent to obtain stainless steel wire; Step 6: Heat the obtained stainless steel wire to 400°C and then soak it in an alkaline mixed solution for 30-60 minutes, then wash it with deionized water for 3 times, dry it, and then perform wire drawing to obtain alloy stainless steel wire; The formula of the alkaline mixed solution is as follows by mass percentage: NaOH 80%, NaNO3 20%.
[0018] Example 2 A preparation process of alloy stainless steel wire specifically comprises the following preparation steps: Step 1: Pour 55 mL of anhydrous ethanol into 30 mL of polyethylene glycol, and perform ultrasonic dispersion treatment for 12 minutes to obtain a mixed solution; Step 2: Add 2.8 g of nano hexagonal boron nitride to the mixed solution of step 1, and continue ultrasonic treatment for 28 min; Step 3, add the weighed powders: 9.5g WC powder, 6.5g Co powder, 3.5g Cr3C2 powder, 0.45g TaC powder, 4.5g Re powder, 2.5g Ru powder, 6.5g rare earth alloy powder, 9.5g graphite powder, wherein the rare earth alloy powder is composed of a mixture of Cu, Ce, and La, and the mass ratio thereof is 0.8:0.4:1.3, and then ultrasonically disperse for 34min; Step 4: After being evenly dispersed, wet ball milling is performed for 68 hours, and then placed in a vacuum drying oven at 114°C for 11 hours, and then sieved with a 105-mesh screen; Step 5, pouring into a high-temperature melting furnace for heating and melting, and then sequentially performing desulfurization, deoxidation, alloying, and refining with a refining agent to obtain stainless steel wire; Step 6: Heat the obtained stainless steel wire to 450° C. and then soak it in an alkaline mixed solution for 40 minutes, wash it with deionized water for 4 times, dry it, and then perform wire drawing to obtain alloy stainless steel wire; The formula of the alkaline mixed solution is as follows by mass percentage: NaOH 75%, NaNO3 25%.
[0019] Example 3 A preparation process of alloy stainless steel wire specifically comprises the following preparation steps: Step 1: Pour 70 mL of anhydrous ethanol into 35 mL of polyethylene glycol, and perform ultrasonic dispersion treatment for 14 minutes to obtain a mixed solution; Step 2: Add 3.2 g of nano hexagonal boron nitride to the mixed solution of step 1, and continue ultrasonic treatment for 32 minutes; Step 3, add the weighed powders: WC powder 10.5g, Co powder 8.5g, Cr3C2 powder 5.5g, TaC powder 0.55g, Re powder 5.5g, Ru powder 3.5g, rare earth alloy powder 7.5g, graphite powder 11g, wherein the rare earth alloy powder is composed of a mixture of Cu, Ce, and La, and the mass ratio thereof is 0.8:0.5:1.6, and then ultrasonically disperse for 38min; Step 4: After being evenly dispersed, wet ball milling is performed for 70 hours, and then dried in a vacuum drying oven at 118°C for 12 hours, and then sieved with a 115-mesh screen; Step 5, pouring into a high-temperature melting furnace for heating and melting, and then sequentially performing desulfurization, deoxidation, alloying, and refining with a refining agent to obtain stainless steel wire; Step 6: Heat the obtained stainless steel wire to 550° C. and then soak it in an alkaline mixed solution for 50 minutes, wash it with deionized water for 4 times, dry it, and then perform wire drawing to obtain alloy stainless steel wire; The formula of the alkaline mixed solution is as follows by mass percentage: NaOH 78%, NaNO3 22%.
[0020] Example 4 A preparation process of alloy stainless steel wire specifically comprises the following preparation steps: Step 1: Pour 75 mL of anhydrous ethanol into 40 mL of polyethylene glycol, and perform ultrasonic dispersion treatment for 15 minutes to obtain a mixed solution; Step 2: Add 3.5 g of nano hexagonal boron nitride to the mixed solution of step 1, and continue ultrasonic treatment for 35 min; Step 3, add the weighed powders: 12.5g WC powder, 9.5g Co powder, 6.5g Cr3C2 powder, 0.65g TaC powder, 7.5g Re powder, 4.5g Ru powder, 8.5g rare earth alloy powder, 12g graphite powder, wherein the rare earth alloy powder is composed of a mixture of Cu, Ce, and La, and the mass ratio thereof is 0.8:0.3:1.6, and then ultrasonically disperse for 40min; Step 4: After being evenly dispersed, wet ball milling is performed for 72 hours, and then dried in a vacuum drying oven at 120°C for 12 hours, and then sieved with a 120-mesh screen; Step 5, pouring into a high-temperature melting furnace for heating and melting, and then sequentially performing desulfurization, deoxidation, alloying, and refining with a refining agent to obtain stainless steel wire; Step 6: Heat the obtained stainless steel wire to 600° C. and then soak it in an alkaline mixed solution for 60 minutes, wash it with deionized water for 5 times, dry it, and then perform wire drawing to obtain alloy stainless steel wire; The formula of the alkaline mixed solution is as follows by mass percentage: NaOH 80%, NaNO3 20%.
[0021] Comparative Example 1 Compared with Example 1, the difference is that no rare earth alloy powder is added; the rest remains unchanged.
[0022] Comparative Example 2 Compared with Example 1, the difference is that no graphite powder is added; the rest remains unchanged.
[0023] Vickers hardness test: DHV-1000 Vickers hardness tester was used for testing. The test parameters were as follows: the load applied to the probe was 200 gf, and the probe tapping time was 10 s. The results are shown in Table 1.
[0024] Tensile strength test: The test was carried out using an electronic universal testing machine with the test parameters of a preload of 50 kN and a tensile rate of 2 mn / min. The results are shown in Table 1.
[0025] Corrosion resistance test: Test according to GB / T 19746-2005, prepare simulated seawater: dissolve 486.2g potassium chloride, 140.7g sodium bicarbonate, 70.4g potassium bromide, and 2.1g sodium fluoride in distilled water or deionized water, and dilute to 7L to obtain a neutral salt solution with a concentration of 35g / L±1g / L. Store the prepared artificial seawater in a sealed glass container for later use; use a potentiometer method to measure the pH value of the solution at 25℃±2℃. If the pH value is not within the range of 6.0-7.0, add analytical pure dilute hydrochloric acid or sodium hydroxide solution to adjust the pH value. Immerse the sample completely in the test solution. The volume of the test solution and the surface area of the sample should not be less than 3L / dm 2 The test temperature is 60℃±2℃, and the continuous immersion is 3000h. After the test, take out the sample, clean the surface with distilled water and dry it, and check whether there are defects such as rust, cracks, bubbles, etc. on the surface of the sample. The results are shown in Table 1.
[0026] Microhardness / HV Tensile strength / MPa Surface state Example 1 953 4887 No rust, no cracks, no bubbles Example 2 948 4862 No rust, no cracks, no bubbles Example 3 942 4545 No rust, no cracks, no bubbles Example 4 940 4537 No rust, no cracks, no bubbles Comparative Example 1 921 4436 Large area of rust, a small amount of cracks, and a large number of bubbles on the surface Comparative Example 2 908 4413 Small area of rust, no cracks, a small amount of bubbles on the surface Wear resistance test: The HT-4001 reciprocating wear tester was used for testing, with a Ø5.5mm SiN4 ceramic ball, a load of 5N, a frequency of 2Hz, a reciprocating distance of 5mm, and a friction time of 20min. The results are as follows Figure 1 As shown: compared with comparative examples 1-2, the wear scar diameter of examples 1-4 is significantly reduced.
[0027] Meanwhile, the contents not described in detail in this specification belong to the prior art known to those skilled in the art.
[0028] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0029] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. An alloy stainless steel wire, characterized in that: The invention is prepared from the following raw materials in parts by weight: 8.5-12.5 parts of WC powder, 5.5-9.5 parts of Co powder, 2.5-6.5 parts of Cr3C2 powder, 0.35-0.65 parts of TaC powder, 3.5-7.5 parts of Re powder, 1.5-4.5 parts of Ru powder, 5.5-8.5 parts of rare earth alloy powder, and 8.5-12 parts of graphite powder; The rare earth alloy powder is composed of a mixture of Cu, Ce and La, and the mass ratio thereof is 0.8:(0.3-0.5):(1.2-1.6).
2. A process for preparing the alloy stainless steel wire according to claim 1, characterized in that: The specific preparation steps include: Step 1, pouring anhydrous ethanol into polyethylene glycol, and performing ultrasonic dispersion treatment to obtain a mixed solution; Step 2: Add nano hexagonal boron nitride to the mixed solution of step 1, and continue ultrasonic treatment; Step 3, adding the weighed powders and then dispersing by ultrasonic treatment; Step 4: After being evenly dispersed, wet ball milling is used, and then drying is carried out in a vacuum drying furnace, and then sieving is carried out using a sieve; Step 5, pouring into a high-temperature melting furnace for heating and melting, and then sequentially performing desulfurization, deoxidation, alloying, and refining with a refining agent to obtain stainless steel wire; Step 6: Heat the prepared stainless steel wire to 400-600°C and then soak it in an alkaline mixed solution for 30-60 minutes, then wash it with water, dry it, and then draw it to obtain alloy stainless steel wire.
3. The process for preparing the alloy stainless steel wire according to claim 2, characterized in that: In the step 1, the ultrasonic dispersion treatment is performed for 10-15 minutes.
4. The process for preparing the alloy stainless steel wire according to claim 2, characterized in that: In the step 2, the ultrasonic dispersion treatment is performed for 25-35 minutes.
5. The process for preparing the alloy stainless steel wire according to claim 2, characterized in that: In the step 3, the ultrasonic dispersion treatment is performed for 30-40 minutes.
6. The process for preparing the alloy stainless steel wire according to claim 2, characterized in that: In the step 4, the ball milling time is 66-72 hours.
7. The process for preparing the alloy stainless steel wire according to claim 2, characterized in that: In step six, the formula of the alkaline mixed solution is as follows by mass percentage: NaOH 75%-80%, NaNO3 20%-25%.
8. The process for preparing the alloy stainless steel wire according to claim 1, characterized in that: In the step six, deionized water is used for washing 3-5 times.
Citation Information
Patent Citations
A nickel-cobalt alloy stainless steel wire and its production process
CN114700383B